HUBUNGAN BRAND TRUST DENGAN KEPUASAN KONSUMEN SMARTPHONE XIAOMI REDMI 5 DI KOTA BENGKULU - Siti Hanila; Nur Fitri Wulandari (Unib Press Universitas Bengkulu, 2019)
Brand trust is a factor that makes a company's success in consumer interest to make purchases while satisfying consumers. Satisfaction will be achieved and enjoyed if it is able to provide value relative to consumer desires. The large number of smartphone products with various brands that have sprung up in the market, has made business competition between smartphone products even tighter. The Xiaomi Redmi 5 smartphone product is one of the smartphone products that is currently quite popular among the public. To maintain the consistency of Xiaomi Redmi 5 smartphone products on the market, smartphone product manufacturer Xiaomi Redmi 5 must continue to be able to maintain consumer confidence in its products so that consumers will reflect brand reliability and brand intention from the Xiaomi Redmi 5 smartphone products it uses. The purpose of this study was to determine the relationship between brand trust and consumer satisfaction at Xiaomi Redmi 5 smartphone in Bengkulu City. This study is a correlational study with the type of data used are primary data obtained through questionnaires. The sample in this study were consumers of Xiaomi Redmi 5 smartphone products who bought smartphones in the Xiaomi City of Bengkulu Gallery totaling 39 people with the sampling method, namely accidental sampling. Data analysis methods used are analysis of average distribution, spearman rank correlation (spearman rank corellation) and hypothesis testing. The results of this study indicate that, there is a strong and significant relationship between brand trust and the satisfaction of Xiaomi Redmi 5 smartphone consumers in Bengkulu City with a correlation coefficient (correlation coefficient) of 0.799 and a probability value (sig) of 0.000 <alpha 0.05.